Childhood constipation: finally something is moving!. (2nd January 2016) - Koppen, Ilan J.N.; Di Lorenzo, Carlo; Saps, Miguel; Dinning, Phil G.; Yacob, Desale; Levitt, Marc A.; Benninga, Marc A.
Abstract : Recent developments in the evaluation and treatment of childhood constipation are likely to influence the way we deal with pediatric defecation disorders in the near future. Innovations in both colonic and anorectal manometry are leading to novel insights into functional defecation disorders in children. Promising results have been achieved with innovative therapies such as electrical stimulation and new drugs with targets that differ from conventional pharmacological treatments. Also, new surgical approaches, guided by manometric findings, have led to improvement in patient outcome. Finally, utilization of non-pharmacological interventions such as fiber and probiotics has been a field of particular interest in recent years. The aim of this article is to provide an update on these and other novel diagnostic and therapeutic tools related to childhood constipation.